2015
DOI: 10.1111/hsc.12217
|View full text |Cite
|
Sign up to set email alerts
|

Priorities, concerns and unmet needs amongHaitians inBoston after the 2010 earthquake

Abstract: In January 2010, a massive earthquake struck Haiti. The devastation not only affected those living in Haiti at the time but also those Haitians living in the United States (U.S.). Few studies have assessed the degree of impact of the earthquake in U.S. Haitian communities. The purpose of this study was to elicit information about health priorities, concerns and resources needed to improve the delivery of health and social care for Haitians in Boston, MA. We conducted six focus groups among 78 individuals in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 41 publications
0
8
0
7
Order By: Relevance
“…35 After the earthquake, studies that investigated the mental health of Haitians in the Haitian diaspora showed that these Haitians experienced more symptoms of distress, psychotrauma, anxiety, and depression. 27,3034 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…35 After the earthquake, studies that investigated the mental health of Haitians in the Haitian diaspora showed that these Haitians experienced more symptoms of distress, psychotrauma, anxiety, and depression. 27,3034 …”
Section: Discussionmentioning
confidence: 99%
“…The consequences of the earthquake were important not only for Haitians living in Haiti but also for Haitians living in the United States, who were watching the devastation and desolation on television and social networks. 27 It can be hypothesized that hosting friends or family members who were displaced from Haiti because they became homeless is a factor in the reactivation of the host’s traumatic memories, triggered by refugees’ narration of the disaster. As such, although hosting refugees can be thought of as a unique opportunity to help one’s community, 27,48 it comes with a risk of weakening one’s own mental health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations